IMPLEMENTATION OF PHYSICAL FITNESS EXERCISES TO IMPROVE LEARNING OUTCOMES OF PHYSICAL EDUCATION, SPORTS AND HEALTH OF STUDENTS OF SMAS AL-AZHAR MEDAN - Jihan Nadia Shyba; Rameyza Zalfa Zahira; Dika Naufal Najwi Siregar; Bayu Prastya; Alif Risqillah (CV. RADJA PUBLIKA, 2024)
This study aims to evaluate the implementation of physical fitness gymnastics in improving learning outcomes of Physical Education, Sports, and Health (PJOK) at Al-Azhar Private High School, Medan. Physical fitness gymnastics is carried out every Wednesday as part of PJOK learning, with the hope of improving students' physical fitness and learning motivation. The research method uses a qualitative approach with the DDAER model (Diagnosis, Design, Action, Evaluation, Reflection) developed by Mulyati Ningsih (2011). The subjects of the study consisted of students who were actively involved in PJOK activities at Al-Azhar Private High School, Medan. Data collection was carried out through observation, interviews, and questionnaires. The results of the study showed that the implementation of physical fitness gymnastics had a positive impact on student learning outcomes in PJOK subjects, as well as increasing student motivation and participation in physical activities at school. Factors that support the effectiveness of physical fitness gymnastics include students' internal motivation and school environmental support, while inhibiting factors include limited facilities and implementation time. This study concludes that physical fitness gymnastics can be used as an effective learning method in improving the quality of physical education at Al-Azhar Private High School, Medan.